Does the level of leisure-time physical activity after bariatric surgery affect bone parameters? - Alexandre do Santos Cremon; Anselmo Alexandre Mendes; Caio Machado de Oliveira Terra; Leticia Andrade Cerrone; Nelson Nardo Junior (Universidade Federal de Santa Catarina, 2018)
Bariatric surgery (BS) causes an exacerbated loss of body weight and fat, and can promote changes in other body tissues such as bone tissue. The aim of this study was to compare the profile of serum and urinary bone markers and bone mineral density (BMD) of active and sedentary patients after BS. The sample consisted of 89 patients, of both sexes, who underwent BS through the gastric bypass in Roux-Y, between years 2003 and 2013. Anthropometry, body composition, spine and femur BMD was evaluated by dual energy x-ray absormetry (DEXA), as well as biochemical variables through serum collected for the dosage of calcium, osteocalcin and PTH levels, and also 24-hours urine for deoxypyridinoline and calcium. The level of leisure-time physical activity was assessed by questionnaire. Statistical significance was set at 5%. The average age of active and sedentary groups was [51.76 (9.66)] and [47.06 (12.16)] and body mass index [34.98 (6.90)] and [29,26 (5.92)], respectively. There are statistically significant differences in osteocalcin levels between groups (p = 0.021), as well as small effect size observed in the following variables: BMD of the total femur, osteocalcin, deoxypyridinoline and serum calcium (respectively d = 0:36; d = 0:39; d = 00:41 d = 0.3). The incorporation of an active lifestyle demonstrated a positive impact on circulating levels of osteocalcin and other bone parameters, thereby indicating a possible preservation of BMD during the aging process.